The use of virtual reality and physical tools in the development and validation of ease of entry and exit in passenger vehicles - Lawson, Glyn; Herriotts, Paul; Malcolm, Louise; Gabrecht, Katharina; Hermawati, Setia (Elsevier, 2015)
Ease of entry and exit is important for creating a positive first impression of a car and to increase customer satisfaction. Several methods are used within vehicle development to optimise ease of entry and exit, including CAD reviews, benchmarking and buck trials. However, there is an industry trend towards digital methods to reduce the costs and time associated with developing physical prototypes. This paper reports on a study of entry strategy in three properties (buck, car, CAVE) in which inconsistencies were demonstrated by people entering a vehicle representation in the CAVE. In a second study industry practitioners rated the CAVE as worse than physical methods for identifying entry and exit issues, and having lower perceived validity and reliability. However, the resource issues associated with building bucks were recognised. Recommendations are made for developing the CAVE and for combinations of methods for use at different stages of a vehicle’s development.